History of English : a resource book for students - McIntyre, Dan, 1975- (New York : Routledge, 2020)
"History of English provides an accessible introduction for those coming to the topic for the first time and answers why and how English has come to be written and spoken as it is today. Structured to reflect chronological developments, it describes and explains the changes that occurred at all linguistics levels, as well as considering changes in orthography, register and discourse. Moreover, it considers international varieties of Englishes and more recent developments in the history of English. Key features of the new edition include: new examples; wider coverage of varieties of English; expanded section on early English and updated readings. This book provides an engaging introductory textbook that is essential reading for all students of English language and linguistics"--
Origins of English -- The history of English or the history of Englishes? -- Language contact in the Middle Ages -- From Middle English to Early Modern English -- The process of standardisation -- Colonialism, imperialism, and the spread of English -- Moves towards present day English -- Global English and beyond -- Understanding Old English -- Varieties of Old English -- The emergence of Middle English -- Sound shifts -- Writing in Early Modern English -- The development of American English -- International English -- The globalisation of English -- The roots of English -- Regions and dialects -- From Old English to Middle English -- Codification and attitudes towards English -- Further elements of grammar in Early Modern English -- English in the new world -- Present day Englishes -- The future of English? -- Vocabulary and meaning in Old English -- Changes in grammatical gender -- Medieval multilingualism -- Shifting sounds -- The development of a written standard -- The beginnings of global English -- Studying recent change in English -- English in the future -- Commentary on activities -- Glossary of linguistic terms -- Further reading -- Timeline of external events in the history of English -- References -- Index.
Includes bibliographical references and index.
Keywords: English language -- History